Secondary Bacterial Infection in Clinically Suspected Cases of Pulmonary Tuberculosis and Their Antibiotic Sensitivity Pattern (Nepal Medical College Journal, 2025)
Secondary bacterial infection has become one of the most important complications in patients suffering with pulmonary tuberculosis (PTB). The suppression of immunity, which can occur due to T-lymphocyte deficiency during active PTB disease, could be the main reason for the bacterial superadded infections. This aimed to evaluate tuberculosis (TB) status and secondary bacterial infections among them. A total of 400 sputum samples were collected and examined using Ziehl-Neelsen staining method as per revised national tuberculosis control program guidelines and GeneXpert following the WHO guidelines. Those sputum samples were also processed for routine bacterial culture and bacteria were identified by conventional techniques. Antimicrobial sensitivity testing was performed on Mueller-Hinton agar plates with commercially available antibiotic discs using Kirby-Bauer disc diffusion techniques and interpreted as per the guidelines of Clinical and Laboratory Standards Institute (CLSI). A total of 44 (11.0%) samples out of 400 yielded tuberculosis by GeneXpert assay and maximum positivity was noted among the age group 46-60 years (20.4%). The present study showed GeneXpert positivity for the MTB detected rate remained to be 11.0 % (44/400) detected as against smear positivity in only 7.5% (30/400) and this difference was found to be statistically significant (p